Chennakesava cult and dalits - Swami Raju, T., 1959- (Bangalore : BTESSC/SATHRI, 2010)
Study on the Chennakesava cult of Guntur District in Andhra Pradesh, India.
Includes bibliographical references (p. [129]-134).
Keywords: Dalits -- Religious life -- India -- Guntur (District); Vishnu (Hindu deity) -- Cult -- India -- Guntur (District); Folk religion -- India -- Guntur (District)